(untitled) (Bangladesh Medical Journal, 2021)
Optic chiasmatic hypothalamic gliomas are among common primary neoplasm of the optic nerve. It presents with decreased vision as well as features of hypopituitarism due to infiltration of the hypothalamus. In this case report, a young man presented with loss of libido, increased thirst, gradual loss of vision, bilateral optic atrophy and visual field defect. The MRI of sellar and paraseller region showed optic chiasmaticglioma with hypothalamic extension and biochemical parameter showed panhypopituitarism. We diagnosed this patient as a case of Optic chiasmatic hypothalamic gliomas (OCHGS) with panhypopituitarism with partial cranial diabetes insipidus with bilateral primary optic atrophy.The patient underwent surgery after adequate hormonal treatment but died due to post-operative complications Bangladesh Med J. 2020 Sept; 49(3) : 49-52